Mineral nitrogen forms and availability in major soil groups of Orissa as influenced by water regime - KUNDU, D K; SINGH, RAVENDER (The Indian Journal of Agricultural Sciences, 2014)
An experiment was conducted during 2000 to determine forms and availability of mineral nitrogen at Bhubaneshwar, in 12 soils under 5 water regimes, viz 20, 40, 60, 80 and 100% saturation. The NO3-N dominated at -< 40 % saturation, whereas NH4-N dominated at -> 60% saturation. Averaged over the soils, mineral N availability was the lowest at 60-80% saturation. The N availability incieased when soil moisture fell below 60 % or rose above 80 % saturation. Averaged over the water regimes, mineral N availability Was lower in Inceptisols (9.7-14.0 mg N/kg soil) than in Entisols (17.9-19.7 mg N/kg soil) and Alfisols ( 17.8-32.3 mg N/kg soil). The mineral N availability at 40-100% saturation was negatively correlated with pH and electrical conductivity (Be) of soil. In soils at 100% saturation, where mineral N was in NH4 form, the dependence of N availability on pH as well as EC was best described by power-type equations. In partially saturated soils, where mineral N Was either in NO3 or in NO3 plus NH4 forms, the dependence of N availability on pH was best described by simple linear equations, whereas quadratic equations described well the EC-N availability relationships in the soils.